Das Human Kapital - Oded Galor; Omer Moav (Brown University, Department of Economics, 2000)
This paper hypothesizes that the demise of the19th century's European class structure reflects a deliberate transformation of society orchestrated bv the Capitalists. Contrary to conventional wisdom, it argues that the demise of this class structure has been an outcome of a cooperative rather than a divisive process. The research suggests that the transition frorn this class structure rna:v be viewed as the outcome of an optimal reaction process of the Capitalists to the increasing, importance of human capital in sustaining, their profit rates. The paper argues that the process of capital accumulation has graduallv intensified the relative scarcity of labor and has generatcd an incentive to augment labor via hurnan capital accumulation. Due to the complementaritv between phvsical and human capital in production, the Capitalists were among, the prime beneficiaries of the potential accumulation of human capital bv the masses. Thev had therefore the incentive to financiallv support public education that would sustain their profit rates and would improve their economic well being, although would ultimatelv undermine their dynasty's position in the social ladder. The support for public education is unanimous despite the fact that the Capitalists carry the prime financial burden of public schooling. That is, due to the co-existence of credit market imperfections and capital-skill complementaritv, the redistribution associated with public education is Pareto improving. Had Karl Marx been exposed to Garv Becker's Human Capital theory, the socio-political experience of the 20th century might have unfolded in a strikinglv different manner. – Income Distributions ; Education ; Growth ; Class Struggle
Keywords: B10; O10; O40; N30; 330; Klassenkampf; Humankapital; Investition; Entrepreneurship-Ansatz; Wirtschaftsgeschichte; Europa